2016
DOI: 10.1007/s11126-016-9430-6
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Bipolar Disorder Patients in Attention Testing: Comparison with Normal Controls and Among Manic, Depressive, and Euthymic Phases

Abstract: Several studies on cognition in bipolar disorder (BD) have been developed on the last decade. Neuropsychological evaluation of attention in BD patients is fundamental since alterations in attention affect other cognitive functions. Evaluate if performance of BD patients in attention tests varies according to each phase of the disease and verify if there are differences in attention when comparing BD patients with normal controls. The study included 101 BD patients, with ages between 18 and 65 years, being 52 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 29 publications
0
6
0
2
Order By: Relevance
“…The multivariate final model revealed that individuals in the depression phase presented 28.0 times more chances of them having periodontitis than individuals in the mania phase. Studies showed that individuals with BPAD are 3 times more frequent in the depression phase than in the mania phase …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The multivariate final model revealed that individuals in the depression phase presented 28.0 times more chances of them having periodontitis than individuals in the mania phase. Studies showed that individuals with BPAD are 3 times more frequent in the depression phase than in the mania phase …”
Section: Discussionmentioning
confidence: 99%
“…One recurrent and serious mental health condition is the bipolar affective disorder (BPAD). Individuals with BAPD have what is called episodes or phases of extreme mania followed by long periods of depression . BPAD is estimated to have a worldwide prevalence rate of 2%‐5% .…”
Section: Introductionmentioning
confidence: 99%
“…A avaliação da fase da doença e os sintomas que a mesma apresenta é essencial para a compreensão do transtorno. Camelo et al, (2017) avaliaram se o desempenho dos pacientes com TB nos testes de atenção variava de acordo com cada fase da doença, e se há diferença quando comparados com pessoas que não possuem o transtorno. O estudo foi realizado com 101 pacientes diagnosticados com algum tipo de transtorno, com idade entre 18 e 65 anos, sendo 22 maníacos, 27 depressivos, 52 eutímicos, além de 30 pessoas saudáveis.…”
Section: Resultsunclassified
“…Another primary link can be delineated between Attention and Thought Disorder, based on studies showing that increased attentional lapses, distractibility, and impairments in attentional task performance are increased across psychotic disorders (Gold et al, 2019;Ivleva et al, 2012a) and associated with symptoms of schizophrenia (Guastella et al, 2013) and positive schizotypy (Marsh et al, 2017;Mohanty et al, 2008;Siddi et al, 2017). The association of attentional lapses and distractibility with manic symptoms further indicates a primary link between Attention and the Mania subfactor (Camelo et al, 2017;Glaus et al, 2018;Pagliaccio et al, 2017), which is provisionally connected to both the Thought Disorder and…”
Section: Reward Valuationmentioning
confidence: 99%